Recent Advances in Multi-Drug Resistance (MDR) Efflux Pump Inhibitors of Gram-Positive Bacteria S. aureus - Katarzyna Kieć-Kononowicz; Anna Matys; Jadwiga Handzlik (MDPI AG, 2013)
The paper focuses on recent achievements in the search for new chemical compounds able to inhibit multidrug resistance (MDR) mechanisms in Gram-positive pathogens. An analysis of the results of the search for new efflux pump inhibitors (EPIs) for Gram-positive bacteria, which have been performed over the last decade, indicates that almost all efforts are focused on the NorA (MFS) efflux pump in S. aureus. Considering the chemical structures of the NorA EPIs that have been identified, it can be observed that the most active agents belong to the families of compounds possessing conjugated double bonds, e.g., chalcones, piperine-like compounds, N-cinnamoylphenalkylamides or citral amide derivatives. Indole-, dihydronaphthyl-, 2-chloro-5-bromo-phenyl- or piperidine moieties seem to be profitable for the EPI properties, as well. These results, together with an increasing knowledge about a variety of efflux pumps that are involved in MDR of Gram-positive pathogens underline that further search for new EPIs should pay more attention to develop MDR efflux protein targets, including SMR, MATE, ABC or other members of the MFS family.